2007
DOI: 10.1002/jbm.a.31254
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of human mesenchymal stem cells in collagen type I hydrogels

Abstract: The chondrogenic differentiation of bone marrow-derived human mesenchymal stem cells (MSCs) in a collagen type I hydrogel, which is in clinical use for matrix-based autologous chondrocyte transplantation (ACT), was investigated. Collagen hydrogels with 2.5 x 10(5) MSCs/mL were fabricated and cultured for 3 weeks in a serum-free, defined, chondrogenic differentiation medium containing 10 ng/mL TGF-beta1 or 100 ng/mL BMP-2. Histochemistry revealed morphologically distinct, chondrocyte-like cells, surrounded by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 45 publications
5
117
0
1
Order By: Relevance
“…For a long time, BMP-2 has been used as a strong stimulator for osteogenic differentiation of stem cells [35]. In other studies, however, BMP-2 has been applied to promote the chondrogenic differentiation of MSCs as well [24,26]. Meanwhile, it is also believed that BMP-2-induced chondrogenic differentiation of MSCs will eventually lead to hypertrophy and endochondral ossification [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, BMP-2 has been used as a strong stimulator for osteogenic differentiation of stem cells [35]. In other studies, however, BMP-2 has been applied to promote the chondrogenic differentiation of MSCs as well [24,26]. Meanwhile, it is also believed that BMP-2-induced chondrogenic differentiation of MSCs will eventually lead to hypertrophy and endochondral ossification [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In line with increased EdU incorporation in co-culture pellets, 1 cluster contained intracellular cell-cycle regulators, such as CCND1, -2, and -3. The fourth cluster contained two secreted growth factors FGF-1 and BMP-2, both of which are established modulators of chondrocyte proliferation and/or matrix production [24][25][26].…”
Section: Microarray Study Identifies a Group Of Genes Regulated By Thmentioning
confidence: 99%
“…However, Nöth et al reported a contraction of up to 75% in the collagen gels, a process that could be results can be confirmed in in vivo studies, the application of MSCs will be facilitated. Our study does not prodisadvantageous for implantation purposes (33). We chose a low cell concentration for differentiation vide new insights regarding this aspect, but the gelatin hydrogels were found to be a suitable material for either due to the limited nutrient supply expected within the intervertebral disc tissue.…”
Section: Establishing Hypoxic Conditions and Experimental Setup Measumentioning
confidence: 99%
“…The gelatin hydrogels presented here as a model for the preparation of tion within a gelatin matrix. (33,54). However, Nöth et al reported a contraction of up to 75% in the collagen gels, a process that could be results can be confirmed in in vivo studies, the application of MSCs will be facilitated.…”
Section: Establishing Hypoxic Conditions and Experimental Setup Measumentioning
confidence: 99%
“…Attempts to mimic this environment by using hydrogel materials has shown promise in restoring functionally competent cartilage because of the inherent cross-linked hydrogel polymer networks which facilitate efficient transport of nutrients and actively form physical environments similar to that of articular cartilage [17]. Natural hydrogel polymers include chitosan, collagen, hyaluronic acid, gelatin and alginate, whereas synthetic polymers encompass poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(ethylene oxide) (PEO), poly(vinyl alcohol) (PVA), poly(acrylic acid) (PAA) and their copolymers [18][19][20][21][22][23][24]. Typically, such hydrogel materials can be functionalized or assembled with specific functional groups to impart enhanced biocompatible properties.…”
Section: Introductionmentioning
confidence: 99%